Efficient Railway Gauge Conversion with Tunnel reconstruction - Seba Minsili, Lezin; Mbessa, Michel; Nzie, Wolfgang; Chiabi Nuh Mih, Rodney; Ndjegwes, Christian Magloire (Journal of Railway Transportation and Technology, 2024)
The modernization of railway networks constructed during the colonial era requires the conversion of railway gauges from the metric to the standard gauge, as well as the expansion from single-track operation to a dual-track operation in order to accommodate railway infrastructures with the traffic growth. Existing critical infrastructures such as bridges and tunnels in the existing network will also require appropriate reconstruction measures since minimum clearance requirements associated with the standard gauge are subjected to new rolling stock and maintenance facilities. The present work presents an optimal procedure to solve efficiently the problem of a tunnel reconstruction during track conversion while maintaining trains circulation during the transition period from metric to standard gauge with less traffic interruption. From a multi-criteria comparison scheme we examine different options ranging from enlarging the existing tunnel to constructing an adjacent new standard gauge dual-track tunnel with the construction of an adjacent standard gauge single-track tunnel as a neutral choice. Results show that enlarging the existing tunnel under a sustained traffic, is both technically feasible and economically viable.